The effects of business environments on corporate strategies and performance of construction organisations - Oyewobi, LO; Windapo, AO; Cattell, KS; Rotimi, J.O.B. (Association of Researchers in Construction Management (ARCOM), 2013)
The study examines the moderating effects of business environment in the relationship between strategies used by construction organisations and examines how these can be used in attaining competitive advantage, and improved corporate performance. The grounds for the examination stems from arguments by researchers that efficient and effective business strategy is an essential tool employed by organisations to direct their business endeavours to the ever changing business environment and record continuous improved performance. The study involves a meta-study of extant literature on construction business environments and business strategies in-use. From this approach, a conceptual framework is proposed for relating business environment and corporate strategies used by construction organisations to their corporate performance that could serve as the basis for further studies in construction organisation strategic planning. Preliminary results of a pilot survey to examine the moderating effects of environmental dimensions on strategies and organisational performance are provided in support of the concept developed. The results reveal that organisations adopt differentiation strategies to ensure survival in a complex business environment. It thus concluded that dimensions of business environment have moderating effects on organisational strategies and performance.
Keywords: Business strategy; Competitiveness; Corporate planning; Organisation